BALANCING INNOVATION AND ETHICS: A GOVERNANCE FRAMEWORK FOR SECURE HYBRID LEARNING ENVIRONMENTS - mukromin mukromin; Tun Lin; Soe Thu Zaw (Journal Neosantara Hybrid Learning, 2026)
Rapid digital transformation in education has accelerated the adoption of hybrid learning systems, yet concerns regarding ethical governance, data security, and institutional accountability remain insufficiently addressed across global contexts. This study aims to develop a governance framework that balances innovation and ethics in secure hybrid learning environments. A qualitative research design using systematic literature review and conceptual analysis was employed, drawing on peer-reviewed studies, policy documents, and institutional reports related to educational technology governance, digital ethics, and cybersecurity in hybrid learning systems. Findings reveal that technological innovation in hybrid learning significantly enhances accessibility and instructional flexibility, while governance deficiencies increase risks related to data privacy, ethical inconsistency, and cybersecurity vulnerabilities. The results further indicate that effective hybrid learning requires an integrated governance framework that aligns innovation strategies with ethical principles and security protocols. Institutions with stronger governance structures demonstrate higher levels of trust, system stability, and educational effectiveness. The study concludes that balancing innovation and ethics through a structured governance framework is essential for ensuring secure, sustainable, and trustworthy hybrid learning environments in the digital era.